Experimental behaviour of three-leaf stone masonry walls - Oliveira, Daniel V. (2006)
A major part of historical structures, currently in European urban centres, is built with stone masonry walls, often constituted by multiple leaves. A common typology encountered is the three-leaf stone masonry wall, which is characterized by a substantial presence of voids in the inner leaf and prone to brittle collapse mechanisms. Nevertheless, the knowledge of the mechanical behaviour of three-leaf masonry walls and guidelines for proper design and control ofthe interventions are limited. A comprehensive experimental study on the structural behaviour of three-leaf stone masonry walls has been planned at University of Minho, considering different strengthening techniques using GFRP (glass fibre reinforced polymer) materials, pozzolana-lime based mortar and lime-based grout. In the paper the first experimental results on materials and three-leaf stone masonry walls are presented and discussed.